Haunted by the event: A response. (2nd April 2020) - Nijhawan, Michael
ABSTRACT: This paper offers a response to contributions by Conerly Casey, Patrick Eisenlohr, Raji S. Soni and Connor VanderBeek in this inaugural theory colloquium in Sikh Formations . By drawing on Derrida's philosophy of event and eventfulness and Veena Das' work, I shall rethink some of the critiques and lines of argument emerging from the four contributions gathered here. Couching my response in the contemporary context of migrant precarity and state violence, I offer some further thoughts as to how Precarious Diasporas might be useful to (re)imagine anthropological inquiry in a transnational field and across sites of diasporicity, religiosity and subjectivity.